A Case of Lafora Disease Diagnosed by Axillary Skin Biopsy - Elife KIMILOĞLU; Pelin AKBAŞ; Özgül ESEN ÖRE; Çağla TURAN (Federation of Turkish Pathology Societies, 2021)
Lafora disease is a severe form of progressive myoclonic epilepsy with autosomal recessive inheritance diagnosed by inclusion body in biopsy. A 26-year-old woman was admitted due to complaints of frequent twitches and fainting. The 0.5x0.3x0.3 cm axillary skin punch biopsy was subjected to routine histopathological evaluation. Cytoplasmic PAS-positive inclusion bodies were observed at the basal side of the eccrine and apocrine glands. The diagnosis of Lafora disease can also be made by the observation of the polyglycosan cytoplasmic inclusion bodies in the brain, liver and skeletal muscle biopsies. Although we need more work to understand the etiopathogenesis of Lafora disease, we would like to draw attention to the importance of skin biopsy in the differential diagnosis of young patients with clinically refractory epilepsy, myoclonus, and cognitive decline.